Pengaruh Strategi Pembelajaran SETS (Science, Environment, Technology, Society) Dipadu Blended Learning Terhadap Kualitas Proses dan Persepsi Mahasiswa - Yatni, Asmaria Nursuci (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aim to study were to determine 1) the quality of the learning process, and 2) students’ perceptions of the learning. One of the strategies that could accommodate the learning is SETS approach combined with blended learning. The research used posttest only control design. The samples were IV semester students who took chemistry environmental course which were consisted of class A (experimental group) class B (control group). The data were of quality of the learning process obtained using observation sheets and studentâ€™s perception which is obtained with questionnaire.The results of the study were as follows. First, the quality of the learning process by using SETS learning strategies combined with blended learning was better than by using SETS learning strategies only. Second, students’ perceptions of learning by using SETS learning strategies combined with blended learning were more positive than using blended learning only.